Perceived Organizational Support On Civil Servant Perfomance With Career Development and Work Motivation As Mediation at The West Sumatera Regional Police - Deswita Deswita; Yunia Wardi (Kirana Publisher (KNPub), 2026)
This study aims to analyze the influence of perceived organizational support on the performance of Indonesian National Police Civil Servants (PNS) at the West Sumatra Regional Police, with career development and work motivation as mediating variables. This study used a quantitative approach with a survey method. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results showed that not all relationships between variables were positive. Several variables demonstrated a significant negative effect on employee performance. This finding indicates that increased perceived organizational support and career development do not always lead to improved performance, especially when their implementation does not align with employee expectations. Furthermore, work motivation was shown to act as a mediating variable explaining the relationship between organizational variables and performance. This study implies that organizations need to consider aspects of fairness, transparency, and policy appropriateness in human resource management to optimally improve performance.